SERVICE SYSTEM FOR GRANTING PERMITS AT THE ONE STOP INTEGRATED PERMIT SERVICE OFFICE (DPMPTSP) IN MAKASSAR CITY - Siti Nurhalizha; Muhammad Nur Yamin; Muhammad Darwis (Jurnal Aktor, 2026)
This research aims to determine the SOP for licensing via e-government in Makassar City. This type of research is descriptive with qualitative research, which is research to answer a problem in the context of the time and situation concerned. The data collection techniques used were observation, interviews and documentation. The results of the discussion in this research were carried out using 3 elements, namely: Support. The first and most important element in the Operational Standards for Licensing Services Through E-Government without any support from the government, local communities or other policy stakeholders. Operational Standards for Licensing Services Through E-Government will not work as it should, so support is needed so that Licensing Services via E-Government can be realized in society.  Capacity (Resources) Competent and qualified human resources for management and access to information technology to ensure Licensing Services via E-Government run as expected at the Makassar City DMPTSP Office. Regarding human resources at the Makassar City DMPTSP Office. Value (Benefits) Benefits of Operational Standards for Licensing Services through the E-Government Application (SIMBG) should be felt by the wider community whatever system is built if the benefits cannot be obtained. Supporting factors for licensing services through the E-Government application (SIMBG) at the Makassar City DMPTSP Office.